Fine tuning of the redox-active diguanidine ligand in cationic cobalt complexes for electronic structure control - Osterbrink, Johanna; Kaliske, Meret; Schulz, Maximilian; Koepcke, Hanna; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2025)
In this work we show that the redox chemistry of hexacoordinated cobalt complexes with redox-active diguanidine ligands could be tuned by modifying the diguanidine and/or the co-ligands. In this way, one-electron oxidation could be directed to be either ligand- or metal-centered, leading to high-spin CoII complexes with an oxidized, radical-monocationic diguanidine ligand (ligand-centered oxidation) or low-spin CoIII complexes with a reduced, neutral diguanidine ligand. Further fine-tuning of the redox-active diguanidine ligand leads to a harmonization of the energies of both redox isomers. Consequently, ligand- as well as metal-centered one-electron oxidation is observed, resulting in a mixture of both redox isomers. Quantum-chemical calculations confirm the energetic proximity of the two redox isomers in this bistable system. The results of this work contribute to the development of a directed approach toward the design of bistable cobalt-guanidine complexes and their possible applications in spin-switching devices.
Gesehen am 24.11.2025